Penerapan Firebase Realtime Database pada Aplikasi E-Tilang Smartphone berbasis Mobile Android - Ilham Firman Maulana (Ikatan Ahli Informatika Indonesia (IAII), 2020)
Traffic violations are familiar things on the highway. For road users who commit traffic violations will be given sanctions such as reprimands, warnings or given a ticket. The speeding ticket is a medium for the police to write fines and violations against road users who commit traffic violations. In this modern era ideas and ideas have emerged to develop a system or application that can facilitate the performance, needs and human activities through an intermediary smartphone. E-ticketing is a digitization of the manual ticketing process that fills offenders data on the ticketing sheet. The e-ticket helps the police in the ticketing process by entering data in the application, utilizing the Firebase Realtime Database technology through smartphone intermediaries. The purpose of this study is to create a traffic violator or E-ticketing system using the Firebase Realtime Database technology. Then provide attachments to offenders in the form of notifications through the E-ticket application, and assist the police in an effort to deal with traffic offenders. The results of this study showed 80.5% of respondents rated the Application of Firebase Realtime Database on the Android-based Smartphone Mobile E-Ticket Application in accordance with the needs of the police in carrying out the ticketing process.